التأصيل التربوي للتدريب في ضوء التربية الإسلامية - السهيمي، خضران عبدالله صالح; العطوى، هيفاء أحمد سليم (جامعة ذمار - كلية الآداب, 2023)
يهدف البحث إلى التعرف على الإطار المفاهيمي للتدريب في ضوء التربية الإسلامية، من خلال دراسة كيفية تأصيله، وإعداد منهجية تربوية إسلامية مقترحة له، وتأتي هذه الدراسة استجابة للتطور الحاصل في مفهوم التدريب الذي انتشرت أنشطته انتشارا واسعا في مختلف المجالات في العصر الحديث، وذلك في ضوء فلسفات ونظريات ومبادئ قائمة إلى حد كبير على المفهوم الغربي للتدريب. ولتحقيق أهداف هذه الدراسة استخدم الباحثان المنهج الاستقرائي والاستنباطي، وتوصلا إلى وجود اهتمام كبير بالتدريب في التربية الإسلامية، واشتمال القرآن الكريم، والسنة المطهرة، وآراء السلف الصالح على الكثير من الشواهد والأمثلة الدالة على الأساليب المختلفة للتدريب، كما أن هناك مثالية متكاملة للتدريب في التربية الإسلامية، بشتى الجوانب المتعلقة بالتدريب، والمدرب، ووضع منهجية خاصة له. This study aimed to identify the conceptual framework for training in the light of Islamic education, through investigating its educational rooting and proposing an approach for training in view of Islamic education. This study comes in response to the development of training whose activities spread across various disciplines in modern time. All this has taken place in the light of philosophies, theories and principles that are largely based on the western notion of training. Therefore, to achieve the questions of the study, the researchers used the inductive and deductive method, through which they concluded that there is a great interest in training in Islamic education. The concept of training is included in the Holy Qur’an, the purified Sunnah, and the opinions of the righteous predecessors. All cover a lot of evidence and examples indicating the different methods of training. It has also been found that there is an integrated idealism for training in Islamic education, in all its related aspects, the trainer, and the development of a special methodology for it.
Keywords: التربية الإسلامية -- البرامج التدريبية -- التأصيل التربوي